FACTORES ASOCIADOS CON EL ESTADO NUTRICIONAL DE LOS NIÑOS Y NIÑAS EN EL PERÚ - Agüero Palacios, Ysela Dominga (2012)
The objective is identify associated factors with nutritional status of under 5 years children in Peru. Was considered a sample of 8103 children under 5 years. Fits GLM logit model, and found that factors significantly associated with the prevalcncc of chronic malnutrition are birth weight (OR:2,3; IC:1,8-2,8) , severe anemia presence(OR:2,3; IC:1,2-4,5), in rural zone households (OR:1,1; IC:1,l-1,5), this prevalence significantly increases with birth order, and poverty, youth, and the low education of the mother. The majority of identified risk factors can be controlled with the reduction of poverty, adequate prenatal monitoring and improved quality of life and education of mothers, especially in rural areas.